Use of autologous mesenchymal stem cells in the combined treatment of symptomatic epilepsy - F. P. Khlebokazov; T. V. Dokukina; N. Yu. Paramonova; S. I. Gotto; I. I. Khvostova; N. N. Misyuk; A. I. Martynenko; Е. L. Slobina; I. V. Shamruk (Эпилепсия и пароксизмальные состояния)
This article presents the results of the clinical application of the method of transplantation of autologous bone marrow stem cells in the treatment of a patient with pharmacoresistant epilepsy, the effectiveness of combination therapy, including antiepileptic drugs and autologous bone marrow stem cells and assess the feasibility, tolerability of this kind of local treatment. The encouraging results of the effectiveness of the proposed method of treatment of pharmacoresistant epilepsy on the clinical case of one patient have been obtained, which requires further study of the clinical application of the AMSC CM transplantation method on a more significant number of clinical cases in larger clinical trials.